Paradigma Ekologis Dalam Tafsir Al-Qur’an: Kajian Tematik-Kontekstual - Febri Hijroh Mukhlis (QOF, 2022)
This paper provides a detailed analysis of the Qur'an's teachings on environmental protection. First, the Qur'an provides an overview of the creation of the universe through its verses. The verses also define numerous natural terms, such as living things, plants, soil, and water, among others. Second, the Qur'an explains that human intervention is necessary to maintain the balance of nature. Therefore, the Qur'an emphasizes that humans are responsible for maintaining, caring for, and preserving their living environment. Even the Qur'an provides a stern warning to humans who harm the environment. The Qur'an provides several concepts of environmental sustainability, including gratitude for the gift of natural resources, respect for nature, and stewardship of the natural environment. The way these ecological verses are explained demonstrates that the Qur'an is highly relevant and even contextual to the issue of environmental degradation. To protect and preserve nature, it is necessary to conduct a study of interpretation using an ecological paradigm